PENGARUH SOCIAL MEDIA MARKETING, PERCEIVED QUALITY, DAN BRAND AWARENESS TERHADAP MINAT BELI KONSUMEN TOTE BAG RUDOFF - Gouwendra, Soni Surya; Dr. Hermeindito, S.E., M.M., Dr. Hermeindito, S.E., M.M. (Universitas Ciputra Surabaya, 2023)
Abstract: This study aims to examine the influence of social media marketing, perceived quality and brand awareness on purchase intention. The respondents were 95 consumers of Rudoff's Tote Bag taken by purposive sampling method. The analysis use multiple regression analysis. The independent variables are social media marketing, perceived quality and brand awareness, while the dependent variable is purchase intention. The results of F test indicate that the regression model used in the study is declared feasible. The results of the t test analysis show that the variables of social media marketing, perceived quality and brand awareness partially have a significant positive effect on consumer’s purchase intention in Rudoff's Tote Bag. So it can be concluded that if each social media marketing, perceived quality and brand awareness is getting better it will be able to increase the consumer’s purchase intentions.